Maspin expression is frequent and correlates with basal markers in triple-negative breast cancer - Sagara Yasuaki; Sagara Yoshiaki; Rai Yoshiaki; Souda Masakazu; Ohi Yasuyo; Umekita Yoshihisa; Tamada Shugo; Tanimoto Akihide (BMC, 2011)
Abstract Background Maspin is a unique member of the serine protease inhibitor superfamily and its expression is found in myoepithelial cells of normal mammary glands; therefore, it has been considered to be a myoepithelial marker. We previously reported that maspin was frequently expressed in biologically aggressive breast cancers. In turn, triple-negative (TN) breast cancer is a subtype of tumor with aggressive clinical behavior and shows frequent expression of basal markers. We hypothesized that maspin expression may be frequent and correlate with basal rather than myoepithelial markers in TN breast cancer. Methods Paraffin-embedded 135 TN invasive ductal carcinoma tissue samples were immunohistochemically investigated using the Dako Envision+ kit and primary antibodies for maspin, basal (CK5/6, EGFR, CK14) and myoepithelial markers (p63, CD10). The correlation between maspin expression and relapse-free survival (RFS) was investigated by the log-rank test. Results The positive rate for maspin was 85.9% and significantly correlated with younger age (P = 0.0015), higher histological grade (P = 0.0013), CK5/6 positivity (P < 0.0001), CK14 positivity (P = 0.0034) and the basal-like subtype defined by CK5/6, EGFR and CK14 positivity (P = 0.013). The positive rates for CK5/6, EGFR, CK14, CD10 and p63 were 59.2%, 48.9%, 34.1%, 17.8% and 12.6%, respectively. There was no significant correlation between maspin expression and RFS. Conclusions The positive rate for maspin is the highest among known basal and myoepithelial markers, and strongly correlates with basal markers in TN breast cancer. These results suggested that maspin could be a candidate for a therapeutic target for TN breast cancer.